Deep Well Injection Induced Seismicity - Dario Rosidi (Institute of Research and Community Outreach - Petra Christian University, 2022)
Injection of fluid into subsurface geologic strata for geothermal energy, oil production, and waste disposal has been linked to induced seismic activity in the United States as well as in several other countries. According to the report of the National Research Council of United States of America thousands of induced earthquakes were reported at the numerous sites, where oil and gas recovery and waste disposal activities took place. Most of these induced earthquakes were small magnitude events (Moment Magnitude [Mw] < 4), although earthquakes of magnitude (Mw) 6.5 to 7 were also reported near the oil and gas production sites. This paper presents the results of a review of case histories on increased seismic events due to deep well injection (DWI) and oil extraction. Key factors that may lead or contribute to increased seismicity will also be discussed.